Understanding and Addressing the Challenges of Gastrointestinal Stromal Tumor (GIST): Towards Improved Diagnosis and Treatment Strategies - Ali Ramzi; Alma Dyah Perwita; Dinda Salsabila; Trisna Ayu Kurnia Putri; Ulul Azmi (Syntax Corporation Indonesia, 2023)
Gastrointestinal stromal tumor (GIST) is a prevalent mesenchymal tumor affecting the digestive tract, with the stomach being the most common location. While some GIST cases are sporadic with no known risk factors, certain factors like age and genetic abnormalities increase the risk. Early diagnosis of GIST remains challenging due to atypical symptoms, leading to late diagnoses and reduced survival rates. This research aims to identify specific risk factors related to local populations, develop accurate early diagnosis methods, and formulate more effective treatment strategies. The study involves a retrospective observational approach, collecting data from medical records of GIST patients and analyzing risk factors and treatment outcomes. The results highlight the increasing prevalence of GIST globally, emphasizing the need for increased awareness and early diagnosis. Challenges in early diagnosis and treatment underscore the importance of public awareness, medical education, and collaborative efforts for better GIST management. This research offers implications for the development of diagnostic guidelines and more effective treatment approaches, ultimately improving the prognosis and quality of life for GIST patients.